(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
Over the past decade, the evolution of embedded system has taken place drastically as it has been for their integration in various industries. This increases Electro-Magnetic Interferences (EMI) problems and generates new design constraints on Electro-Magnetic Compatibility (EMC). Thus, the nature of the electromagnetic environment and the prospective for undesired coupling must be taken into consideration by embedded systems engineers to avoid the equipment failure or malfunction. Accordingly, the radiated emission models are of great interest to designers of electronic equipment. This paper exploits the Plane Wave Spectrum (PWS) technique to predict and compute the magnetic field at various distances till 100mm above a Device Under Test (DUT). Good similarities are obtained between the magnetic field components calculated by PWS and the simulated ones by HFSS at different elevation from the electric dipole.